Glycogen as a Building Block for Advanced Biological Materials. Issue 18 (16th October 2019) - Besford, Quinn A.; Cavalieri, Francesca; Caruso, Frank
Abstract: Biological nanoparticles found in living systems possess distinct molecular architectures and diverse functions. Glycogen is a unique biological polysaccharide nanoparticle fabricated by nature through a bottom‐up approach. The biocatalytic synthesis of glycogen has evolved over time to form a nanometer‐sized dendrimer‐like structure (20–150 nm) with a highly branched surface and a dense core. This makes glycogen markedly different from other natural linear or branched polysaccharides and particularly attractive as a platform for biomedical applications. Glycogen is inherently biodegradable, nontoxic, and can be functionalized with diverse surface and internal motifs for enhanced biofunctional properties. Recently, there has been growing interest in glycogen as a natural alternative to synthetic polymers and nanoparticles in a range of applications. Herein, the recent literature on glycogen in the material‐based sciences, including its use as a constituent in biodegradable hydrogels and fibers, drug delivery vectors, tumor targeting and penetrating nanoparticles, immunomodulators, vaccine adjuvants, and contrast agents, is reviewed. The various methods of chemical functionalization and physical assembly of glycogen nanoparticles into multicomponent nanodevices, which advance glycogen toward a functional therapeutic nanoparticle from nature and back again, are discussed in detail. Abstract : Glycogen is one of nature's unique biological polysaccharide nanoparticles, which holds promise as a material for biomedical, including therapeutic, applications. The recent literature on advancing glycogen as a building block for advanced biofunctional materials is reviewed.